Risk of neurodevelopmental disorders in the offspring of mothers with a history of endometriosis in Taiwanese women - Pei-Yin Yang; Ching-Ming Wang; Pei-Lun Liao; Jing-Yang Huang; Keng-Wei Liang; Yu-Hsuan Lin; Shun-Fa Yang; Po-Hui Wang (Brain, Behavior, & Immunity - Health)
Several neurodevelopmental disorders have been linked to early life immune activation and inflammation, including developmental delay, cerebral palsy, intellectual disabilities, and other neurodevelopmental and psychiatric disorders. Certain inflammatory cytokines, such as interleukin-1β, interleukin-6, and tumor necrosis factor-α, secreted by endometriosis cells cause chronic pelvic inflammation and pain. The aim of this study was to evaluate whether maternal endometriosis increased the risk of neurodevelopmental disorders in offspring in Taiwanese women. The study included eligible mother–offspring pairs with maternal endometriosis (the case cohort) and mother–offspring pairs without maternal endometriosis (the comparison cohort) matched for maternal age at delivery, infant sex, and delivery date, both with offspring born during 2009–2016 and followed till 2019, from the Taiwan Maternal and Child Health Database. The incidence rates and crude hazard ratios (HRs) of development delay and cerebral palsy in the offspring delivered by mothers with endometriosis were higher than those in the offspring delivered by mothers without endometriosis (developmental delay: incidence 1.51 vs. 1.30 per 1000 person-months, crude HR = 1.16; cerebral palsy: incidence 0.04 vs. 0.03 per 1000 person-months, HR = 1.38). In model 1, the adjusted HRs of development delay and cerebral palsy in the offspring of mothers with endometriosis were 1.16 (95 % confidence interval [CI] = 1.11–1.22, P < 0.0001) and 1.39 (95 % CI = 1.04–1.85, P = 0.0256). In model 2, these were 1.11 (95 % CI = 1.06–1.17) and 1.01 (95 % CI = 0.76–1.36), respectively. However, the HRs of intellectual disabilities and other neurodevelopmental and psychiatric disorders were not significantly different between the offspring of mothers with and without endometriosis. In conclusion, maternal endometriosis may increase the risks of cerebral palsy and specifically developmental delay in offspring.